Lysoquinone-TH1, a New Polyphenolic Tridecaketide Produced by Expressing the Lysolipin Minimal PKS II in Streptomyces albus - Torben Hofeditz; Claudia Eva-Maria Unsin; Jutta Wiese; Johannes F. Imhoff; Wolfgang Wohlleben; Stephanie Grond; Tilmann Weber (MDPI AG, 2018)
The structural repertoire of bioactive naphthacene quinones is expanded by engineering Streptomyces albus to express the lysolipin minimal polyketide synthase II (PKS II) genes from Streptomyces tendae Tü 4042 (llpD-F) with the corresponding cyclase genes llpCI-CIII. Fermentation of the recombinant strain revealed the two new polyaromatic tridecaketides lysoquinone-TH1 (7, identified) and TH2 (8, postulated structure) as engineered congeners of the dodecaketide lysolipin (1). The chemical structure of 7, a benzo[a]naphthacene-8,13-dione, was elucidated by NMR and HR-MS and confirmed by feeding experiments with [1,2-13C2]-labeled acetate. Lysoquinone-TH1 (7) is a pentangular polyphenol and one example of such rare extended polyaromatic systems of the benz[a]napthacene quinone type produced by the expression of a minimal PKS II in combination with cyclases in an artificial system. While the natural product lysolipin (1) has antimicrobial activity in nM-range, lysoquinone-TH1 (7) showed only minor potency as inhibitor of Gram-positive microorganisms. The bioactivity profiling of lysoquinone-TH1 (7) revealed inhibitory activity towards phosphodiesterase 4 (PDE4), an important target for the treatment in human health like asthma or chronic obstructive pulmonary disease (COPD). These results underline the availability of pentangular polyphenolic structural skeletons from biosynthetic engineering in the search of new chemical entities in drug discovery.